DISCOVERING ELT LECTURERS' READINESS IN APPLYING ONLINE LEARNING IN THE POST-PANDEMIC ERA - Maya Defianty; Destina Winarti; Siti Zulfa; Didin Nuruddin Hidayat; Yatni Fatwa Mulyati; Ummi Kultsum (IJEE (INDONESIAN JOURNAL OF ENGLISH EDUCATION), 2023)
ABSTRACT This research aims to identify ELT lecturers' readiness to implement online learning. This research involved 30 ELT lecturers from three different time zones in Indonesia: the western, middle, and eastern parts of Indonesia. The study employed an explanatory mixed method in which the quantitative stage was conducted prior to the qualitative stage. Drawing on data from questionnaires and Focus Group Discussions (FGD), the study found that regardless of the learning mode, lecturers' instruction remains similar except for the assessment process. However, this research also found that geographical location, learning materials, internet connection, and affordability contribute to lecturers' preference in selecting learning modes. This research implies that lecturers are ready to embrace the most of online learning; however, the utmost benefit from online learning can only be attained if the supporting systems are available for both lecturers and students. ABSTRAK Penelitian ini bertujuan untuk mengidentifikasi kesiapan dosen ELT dalam melaksanakan pembelajaran online. Penelitian ini melibatkan 30 dosen ELT dari tiga zona waktu yang berbeda di Indonesia. Berdasarkan data dari kuesioner dan Diskusi Kelompok Fokus (FGD), penelitian ini menemukan bahwa tidak peduli mode pembelajarannya, instruksi dosen tetap sama kecuali dalam proses penilaian. Namun, penelitian ini juga menemukan bahwa lokasi geografis, materi pembelajaran, serta koneksi internet dan ketersediaan anggaran mempengaruhi preferensi dosen dalam memilih mode pembelajaran. Penelitian ini menyiratkan bahwa dosen siap untuk mengadopsi sebagian besar pembelajaran online; namun, manfaat maksimal dari pembelajaran online hanya dapat dicapai jika sistem pendukung tersedia baik untuk dosen maupun mahasiswa. How to Cite: Defianty, M., Winarti, D., Zulfa, S., Hidayat, D.N., Mulyati, Y.F. & kultsum U. (2023). Discovering ELT Lecturers' Readiness in Applying Online Learning in the Post-Pandemic Era. IJEE (Indonesian Journal of English Education), 10(2), 355-373. doi:10.15408/ijee.v10i2.35205.